The food journal of Lewis & Clark : recipes for an expedition - Gunderson, Mary (History Cooks, 2003)
Presented in a chronological style, this book interweaves history and description of the historic Lewis and Clark expedition with discussions of their cooking methods. Includes recipes using food stuffs common in the 19th century, wild foods found along their journey, and some Native American foods.